miRTarBase: a database curates experimentally validated microRNA-target interactions - Hsu, Sheng-Da; Lin, Feng-Mao; Wu, Wei-Yun; Liang, Chao; Huang, Wei-Chih; Chan, Wen-Ling; Tsai, Wen-Ting; Chen, Goun-Zhou; Lee, Chia-Jung; Chiu, Chih-Min; Chien, Chia-Hung; Wu, Ming-Chia; et al. (Nucleic acids research, 2011)
MicroRNAs (miRNAs), i.e. small non-coding RNA molecules (~22 nt), can bind to one or more target sites on a gene transcript to negatively regulate protein expression, subsequently controlling many cellular mechanisms. A current and curated collection of miRNA-target interactions (MTIs) with experimental support is essential to thoroughly elucidating miRNA functions under different conditions and in different species. As a database, miRTarBase has accumulated more than 3500 MTIs by manually surveying pertinent literature after data mining of the text systematically to filter research articles related to functional studies of miRNAs. Generally, the collected MTIs are validated experimentally by reporter assays, western blot, or microarray experiments with overexpression or knockdown of miRNAs. miRTarBase curates 3576 experimentally verified MTIs between 657 miRNAs and 2297 target genes among 17 species. miRTarBase contains the largest amount of validated MTIs by comparing with other similar, previously developed databases. The MTIs collected in the miRTarBase can also provide a large amount of positive samples to develop computational methods capable of identifying miRNA-target interactions. miRTarBase is now available on http://miRTarBase.mbc.nctu.edu.tw/, and is updated frequently by continuously surveying research articles.